Successful colonization of the Red Sea Yellowspotted Puffer, Torquigener flavimaculosus in the Mediterranean without a genetic bottleneck - Yaron Tikochinski; Talya Ohana; Uzi Motro; Daniel Golani (Aquatic Invasions)
The Yellowspotted Puffer Torquigener flavimaculosus (Hardy & Randall, 1983) invaded the Mediterranean from the Red Sea via the Suez Canal. In the present study, we analyzed two mitochondrial loci, the cytochrome c oxidase 1 (COI) and the control region (D-loop), from the Mediterranean and the Red Sea populations. Both the COI and the D-loop showed no decrease of genetic variability in the Mediterranean population compared to the source population from the Red Sea. When comparing the genetic variability to two other species of the Tetraodontidae family (Takifugu rubripes and Takifugu obscurus), the mean divergence within the T. flavimaculosus is almost twice as large. T. flavimaculosus has two distinct genetic groups, similarly represented both in the Red Sea and in the Mediterranean, with similar coefficients of differentiation in COI, in D-loop, and, not surprisingly, in the two genes combined. This suggests that T. flavimaculosus has most likely established a sustainable population in the Suez Canal, that has gradually dispersed northward and eventually entered the Mediterranean with a large number of individuals, carrying a great deal of its genetic variability.